High prevalence of highly pathogenic avian influenza A virus in Vietnam’s live bird markets - Duy Tung Dao; Coleman, K.K.; Vuong N. Bui; Anh N. Bui; Long H. Tran; Quy D. Nguyen; Son Than; Pulscher, L.A.; Marushchak, L.V.; Robie, E.R.; Hung Nguyen-Viet; Phuc Duc Pham; et al. (Oxford University Press, 2024)
Background: In recent years Vietnam has suffered multiple epizootics of influenza in poultry.